What has driven the U.S. monthly oil production since 2009? Empirical results from two modeling approaches - Ramaprasad Bhar; Anastasios G. Malliaris; Mary E. Malliaris (Journal of Risk and Financial Management, 2021)
From the early 1970s to the Global Financial Crisis of 2007-09, U.S. crude oil production followed a declining trend. After the Global Financial Crisis, U.S. crude oil production increased rapidly. This paper addresses the important question "what economic factors have driven U.S. crude oil production since the Global Financial Crisis?". We propose that factors such as: the price of oil, the one period lagged price of oil, the price of copper, the crude oil price volatility, the Trade Weighted U.S. Dollar Index, and the high yield index spread, are important explanatory variables. Using two modeling approaches, namely, multiple regression, and the random tree methodology, we conclude that the one month lagged price of oil is the most significant explanatory variable, among all considered, for the upward trend of U.S. oil production from 2009 to early 2020.
Keywords: 330; decision tree analysis; high yield; oil uncertainty; price of copper; price of oil; U.S. oil production